Changes in peripheral blood indicators and hemostatic system in patients with uterine fibroids - I. V. Savytskiy; A. K. Magdenko; I. A. Kuzmenko; P. E. Grigoriev; I. V. Mjastkivska (Journal of Education, Health and Sport, 2017)
The article presents the results of studying the parameters of peripheral blood and the system of coagulation of patients with uterine fibroids. The analyzed data indicate the presence of a pronounced chronic inflammatory process, which is confirmed by the relevant indicators. The obtained results correlate with the data obtained by other authors. Since in the course of preliminary studies, the expediency of using the buccal epithelium to confirm the diagnosis of "uterine fibroids" has been determined, the blood system parameters have been confirmed once again confirm the high-visibility of this technique.